2010
DOI: 10.5251/ajsms.2010.1.2.191.195
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate governance lead to a change in the capital structure?

Abstract: The study investigates the relationship between corporate governance and capital structure of randomly selected 19 banks of Pakistan. The data was collected from financial statements issued by financial institution and multiple regression model was applied to find the relationship between the variables. Results show that there is no relationship between corporate governance and capital structure in the banking sector of Pakistan. Furthermore, our findings show that all independent variables are positively rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 10 publications
(8 reference statements)
4
15
2
7
Order By: Relevance
“…This results is consistent with prior empirical results reported by Rehman et al (2010).H1b predicts a statistically significant positive relationship between board structure characteristics (BSC) and long term debt ratio (LTDR).H1b was rejected in our current research, as the coefficient on board structure characteristics index (BSCI) is negatively and statistically significant. This result is consistent with prior empirical results reported by Abor and Biekpe (2007).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This results is consistent with prior empirical results reported by Rehman et al (2010).H1b predicts a statistically significant positive relationship between board structure characteristics (BSC) and long term debt ratio (LTDR).H1b was rejected in our current research, as the coefficient on board structure characteristics index (BSCI) is negatively and statistically significant. This result is consistent with prior empirical results reported by Abor and Biekpe (2007).…”
Section: Discussionsupporting
confidence: 82%
“…Finally, table 11 reported the prob>chi2 of 0.000 at 5% significance level, suggesting that our model 1a-STDR is statistically significant. Our empirical results are consistent with prior empirical study reported by Rehman et al (2010), therefore, we rejected the hypothesis H1a. Table 12 presents the regression results from the Panel Corrected Standard Errors (PCSEs) for Model 1b-LTDR.The results indicates that board structure characteristics index (BSCI) has a statistically significant effect on capital structure decision of East African listed firms as measured by long term debt ratio (LTDR) at 5% significance level.…”
Section: Panels Corrected Standard Errors (Pcses) Regression Modelsupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast, Lipton and Llorsch (1992) found that, there is a significant relationship between capital structure and board size. In the supportive way to the findings of Lipton and Llorech, scholars in the finance noted that, corporate governance practices has the significant relationship with capital structure in terms leverage decision in the top level management (Pfeffer & Salancick ,1978;Wen , Rwegasir, & Bilderbeek ,2002;Abor ,2007;Rehman., Rehman, & Raoof , 2010 ). Further, Berger, Ofek, & Yermack (1997) found that firms with larger board membership have low leverage or debt ratio.…”
Section: The One-way Anova (F-test)mentioning
confidence: 95%